2018
DOI: 10.4149/av_2018_101
|View full text |Cite
|
Sign up to set email alerts
|

Status updates of Newcastle disease and amelioration effects of medicinal plants against Newcastle disease virus: A review

Abstract: Recently, medicinal plants are achieving great interest because of their use in ethno medicine treatment of different common diseases and also other medicinal assertions are now reinforced by comprehensive scientific evidence. Almost 82 research articles and abstracts published, so far, were screened for evaluating antiviral efficiency of various plant samples and 23 different plants were found to be traditionally used against Newcastle disease (ND). ND is a most transmissible viral disease of avian species ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…On an initial rigorous, or strict, analysis, removing all potential contaminating human, bacterial or phage sequences, RNA virus sequences in the paramyxovirus ( 28 ) and orthomyxovirus ( 29 ) families were detected. Virus sequence detection was read blinded by four investigators (ST, SS-C, AV, AL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On an initial rigorous, or strict, analysis, removing all potential contaminating human, bacterial or phage sequences, RNA virus sequences in the paramyxovirus ( 28 ) and orthomyxovirus ( 29 ) families were detected. Virus sequence detection was read blinded by four investigators (ST, SS-C, AV, AL).…”
Section: Resultsmentioning
confidence: 99%
“…Both paramyxovirus and orthomyxovirus families have been reported as causes for myocarditis in patients without known prior cancer or chemotherapy. The detectable sequences for orthomyxovirus matched to influenza A ( 29 ) and those for paramyxovirus with avulavirus ( 28 ). On a secondary broad analysis using a customized screen, we were able to detect larger numbers of RNA virus sequences for orthomyxovirus influenza A and paramyxovirus Avulavirus, as well as a larger array of RNA viruses including retroviruses, insect viruses and phage.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the plant species identified in the present study have been reported in previous studies with scientific evidence of their use in poultry. The extracts of these plants, including Acacia nilotica, Withania somnifera, and Azadiractha indica have biological activities against Escherichia coli, Staphyllococcus aureus, Klebsiella pneumoniae and against Newcastle disease and fowl pox viruses (Mohamed et al, 2010;Ashraf et al, 2018). They also act on external parasites and helminths (Carine et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants produce bioactive compounds which are responsible for their therapeutical potentials (Barbieri et al, 2017;Credo et al, 2018). Several medicinal plants have been scientifically confirmed to have anti-NDV activity (Lagu & Kayanja, 2010;Sulaiman et al, 2011;Bakari et al, 2012;Raza et al, 2015;Al-Hadid, 2016;Ashraf et al, 2018;Doostmohammadian et al, 2020;Shahzad et al, 2020) though their bioactive compounds responsible for it, are not mentioned.…”
Section: Introductionmentioning
confidence: 99%